Maternal and Neonatal Outcomes Associated with Amniotomy among Nulliparous Women Undergoing Labor Induction at Term - Battarbee, Ashley N.; Sandoval, Grecio; Grobman, William A.; Reddy, Uma M.; Tita, Alan T.N.; Silver, Robert M.; El-Sayed, Yasser Y.; Wapner, Ronald J.; Rouse, Dwight J.; Saade, George R.; Chauhan, Suneet P.; Iams, Jay D.; Chien, Edward K.; Casey, Brian M.; Gibbs, Ronald S.; Srinivas, Sindhu K.; Swamy, Geeta K.; Simhan, Hyagriv N.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2020)
Objective The aim of the study is to evaluate the association between amniotomy at various time points during labor induction and maternal and neonatal outcomes among term, nulliparous women.Study Design Secondary analysis of a randomized trial of term labor induction versus expectant management in low-risk, nulliparous women (2014–2017) was conducted. Women met inclusion criteria if they underwent induction ≥38 weeks' gestation using oxytocin with documented time and type of membrane rupture. Women with antepartum stillbirth or fetal anomaly were excluded. The primary outcome was cesarean delivery. Secondary outcomes included maternal and neonatal complications. Maternal and neonatal outcomes were compared among women with amniotomy versus women with intact membranes and no amniotomy at six 2-hour time intervals: before oxytocin initiation, 0 to <2 hours after oxytocin, 2 to <4 hours after, 4 to <6 hours after, 6 to <8 hours after, and 8 to <10 hours after. Multivariable logistic regression adjusted for maternal age, body mass index, race/ethnicity, modified Bishop score on admission, treatment group, and hospital (as a random effect).Results Of 6,106 women in the parent trial, 2,854 (46.7%) women met inclusion criteria. Of these 2,340 (82.0%) underwent amniotomy, and majority of the women had amniotomy performed between 2 and <6 hours after oxytocin. Cesarean delivery was less frequent among women with amniotomy 6 to <8 hours after oxytocin compared with women without amniotomy (21.9 vs. 29.7%; adjusted odds ratio 0.61, 95% confidence interval 0.42–0.89). Amniotomy at time intervals ≥4 hours after oxytocin was associated with lower odds of labor duration >24 hours. Amniotomy at time intervals ≥2 hours and <8 hours after oxytocin was associated with lower odds of maternal hospitalization >3 days. Amniotomy was not associated with postpartum or neonatal complications.Conclusion Among a contemporary cohort of nulliparous women undergoing term labor induction, amniotomy was associated with either lower or similar odds of cesarean delivery and other adverse outcomes, compared with no amniotomy.
Keywords: amniotomy; artificial rupture of membranes; cesarean; induction; labor; nulliparous